ANALISIS KEBUTUHAN PENGGUNA DALAM PENGEMBANGAN KOLEKSI DI PERPUSTAKAAN BADAN INFORMASI GEOSPASIAL UNTUK OPTIMALISASI LAYANAN - Septevan Nanda Yudisman; Jalinur Jalinur (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2023)
The Badan Informasi Geospasial (BIG) library is a type of special library that provides services to employees within the BIG. The aim of this research is to determine user information needs by carrying out user needs analysis activities in the collection development process carried out by the BIG Library. The research method applied uses a case study method with a descriptive qualitative research type. Data collection was carried out by means of observation and interviews with the aim of being able to describe a case in detail and in depth, then analysis was carried out by comparing the patterns expected by researchers based on existing literature with the patterns found when conducting research. Research results: BIG Library has consistently carried out collection development activities every year with the aim of meeting the information needs of its users. The BIG Library needs an additional budget to subscribe to scientific journals. As a type of special library in Indonesia, the BIG Library needs to strengthen its repository collection to meet the needs of its users. It is necessary to carry out an in-depth analysis regarding the information needs of users. The BIG library needs to conduct information audits and interviews regarding user information needs periodically in all sections of the BIG).